The Challenges of Students’ Shyness in Speaking English in the Classroom - Andi Fahima Yanti; Muhammad Zailani U Pao; Hijrah Hijrah (Asosiasi Periset Bahasa Sastra Indonesia, 2026)
Shyness is one of the affective factors that often hinders students’ ability to speak English in the classroom, particularly in English as a Foreign Language (EFL) contexts. This study aims to investigate students’ experiences of shyness in speaking English, identify the factors contributing to their shyness, and examine its impact on their speaking learning process. This research employed a qualitative descriptive approach. The participants were junior high school students who were involved in English learning activities during a community service program (KKN). Data were collected through an open-ended questionnaire consisting of 20 questions related to students’ attitudes, feelings, experiences, and coping strategies in speaking English. The findings reveal that most students experience nervousness, fear of making mistakes, and fear of being laughed at by peers when speaking English. Peer reactions, low self-confidence, limited vocabulary, and pronunciation difficulties were identified as the main factors causing shyness. Furthermore, shyness negatively affects students’ participation and willingness to practice speaking English in class. However, supportive teachers, group-based activities, and a relaxed learning atmosphere were found to help reduce students’ shyness. This study suggests that teachers should create a supportive and non-threatening classroom environment to enhance students’ confidence in speaking English.